2008
DOI: 10.1111/j.1095-8649.2007.01724.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tag and suture type on survival and growth of brown trout with surgically implanted telemetry tags in the wild

Abstract: To test the effects of surgical implants with or without external antennae, 188 wild brown trout Salmo trutta, 150-290 mm, were tagged and released in a small river in May 2005. After 5 months, 103 of the fish were recaptured and examined. Thus, information on the relative survival, growth and general condition of each fish was obtained. The relative survival did not differ between the three groups (control, antennae and no antennae), but the specific growth of the two tagged groups were lower than that of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
97
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(102 citation statements)
references
References 33 publications
3
97
2
Order By: Relevance
“…This is similar to a brown trout study that showed that dummy radio transmitters caused negative effects on growth, but the decrease in growth had no negative effects on the survival of brown trout (Jepsen et al 2008). It is difficult to predict whether the bighead carp would die in a longterm study, however our results showed that the bighead carp could survive at least 56 days after surgically implanted with transmitters.…”
Section: Discussionsupporting
confidence: 78%
“…This is similar to a brown trout study that showed that dummy radio transmitters caused negative effects on growth, but the decrease in growth had no negative effects on the survival of brown trout (Jepsen et al 2008). It is difficult to predict whether the bighead carp would die in a longterm study, however our results showed that the bighead carp could survive at least 56 days after surgically implanted with transmitters.…”
Section: Discussionsupporting
confidence: 78%
“…Comparatively little is known about the longerterm consequences of intraperitoneal telemetry transmitters (Tyus 1988), with a deficit of research conducted on unrestrained wild fish. The few longer-term field studies that have been published tended to focus on transmitter retention and fish growth and survival (Jepsen & Aarestrup 1999, Jepsen 2003, Jepsen et al 2008. Such field-based validation studies are critical, as laboratory studies may not reflect the challenges (e.g.…”
Section: Abstract: Telemetry · Fish · Surgical Techniques · Nutritiomentioning
confidence: 99%
“…Most studies evaluating surgical wounds have occurred via holding studies in a laboratory or mesocosms in the field [10][11][12][13][14][15][16][17][18], and a dearth of information exists for rates of healing and suture shedding from free-ranging fishes in the wild (but see [9,19]). Generally, this lack of information stems from a low probability of investigators encountering fish after release to examine surgical incisions.…”
Section: Open Accessmentioning
confidence: 99%